Pituitary Adenylate Cyclase-Activating Polypeptide Reverses Ammonium Metavanadate-Induced Airway Hyperresponsiveness in Rats. (14th June 2015) - Tlili, Mounira; Rouatbi, Sonia; Sriha, Badreddine; Ben Rhouma, Khémais; Sakly, Mohsen; Vaudry, David; Wurtz, Olivier; Tebourbi, Olfa
Abstract : The rate of atmospheric vanadium is constantly increasing due to fossil fuel combustion. This environmental pollution favours vanadium exposure in particular to its vanadate form, causing occupational bronchial asthma and bronchitis. Based on the well admitted bronchodilator properties of the pituitary adenylate cyclase-activating polypeptide (PACAP), we investigated the ability of this neuropeptide to reverse the vanadate-induced airway hyperresponsiveness in rats. Exposure to ammonium metavanadate aerosols (5 mg/m 3 /h) for 15 minutes induced 4 hours later an array of pathophysiological events, including increase of bronchial resistance and histological alterations, activation of proinflammatory alveolar macrophages, and increased oxidative stress status. Powerfully, PACAP inhalation (0.1 mM) for 10 minutes alleviated many of these deleterious effects as demonstrated by a decrease of bronchial resistance and histological restoration. PACAP reduced the level of expression of mRNA encoding inflammatory chemokines (MIP-1α, MIP-2, and KC) and cytokines (IL-1α and TNF-α ) in alveolar macrophages and improved the antioxidant status. PACAP reverses the vanadate-induced airway hyperresponsiveness not only through its bronchodilator activity but also by counteracting the proinflammatory and prooxidative effects of the metal. Then, the development of stable analogs of PACAP could represent a promising therapeutic alternative for the treatment of inflammatory respiratory disorders.